Phylogeny and diversity of Bjerkandera (Polyporales, Basidiomycota), including four new species from South America and Asia - Wang, Chao-Ge; Vlasák, Josef; Dai, Yu-Cheng (MycoKeys, 2021)
Four new species of Bjerkandera, viz. B. ecuadorensis, B. fulgida, B. minispora, and B. resupinata spp. nov., are described from tropical America and Asia. B. ecuadorensis is characterised by dark grey to black pore surface, a monomitic hyphal system, hyaline to yellowish-brown generative hyphae, and ellipsoid basidiospores measuring 3.9-4.5 × 2.7-3 μm. B. fulgida is distinguished from the other species in the genus by clay buff to pale brown and shiny pore surface. B. minispora is characterised by white tomentose pore mouth and small basidiospores measuring 3.1-4.2 × 2-2.8 μm. B. resupinata is characterised by resupinate basidiomata, pinkish buff to pale brownish pore surface, and ellipsoid to broadly ellipsoid basidiospores measuring 4.5-6 × 3.2-4.1 µm. All these new species grow on angiosperm trunks or rotten wood, and cause a white rot. The closely related taxa to four new species are discussed. An identification key to the ten accepted species of Bjerkandera is provided, and a phylogeny comprising all known Bjerkandera species is provided.
Keywords: wood-decaying fungi; polypore; Phylogeny; taxonomy